PHARMACOLOGY OF OBESITY AND RISKS OF DRUGS FOR SLIMMING - Marques, Danielle de Oliveira; Quintilio , Maria Salete Vaceli (Revista Coleta Científica, 2021)
Obesity is currently considered a major public health problem, being responsible for the substantial increase in morbidity and mortality. It also presents itself as a large portion of the pharmaceutical industry, which involves the development of drugs, modified foods and also strategies that encourage dietary re-education and regular physical activity. This Literary Review sought a report on the drugs used to treat obesity and a description of their adverse side effects. Pharmacology for the treatment of obesity poses great health risks when not prescribed and monitored by qualified professionals.